The Pacific (DSDP Site 463) and Tethys Ocean record of OAE1a: a taxonomic and quantitative analyses of planktonic foraminifera - A. Barchetta; M.R. Petrizzo; C. Bottini; E. Erba (Società Geologica Italiana, 2014)
The Selli Level (Early Aptian) is a regional marker-bed identified in the Umbria-Marche area (central Italy) consisting of laminated black shales rich in organic matter, alternated with radiolarian beds. The Selli Level is regarded as the sedimentary expression of the OAE1a (Oceanic Anoxic Event 1a) and is marked by a δ13C anomaly, comprising of a pronounced negative shift followed by a positive excursion. A detailed and quantitative documentation in terms of species identification and distribution, variation of shell size, diversity and abundance of planktonic foraminifera across Selli Level equivalents is presented for a 24 m-thick stratigraphic section of the Cismon core (southern Alps, Italy) and a 60 m-thick stratigraphic interval from DSDP Site 463 (Mid-Pacific Mountains). Foraminiferal quantitative (species richness and abundance) and morphometric analyses (shell size measurements) were conducted on washed residues and thin sections. Results from the Cismon Core allow identification of three intervals (below, within and above the Selli Level equivalent) characterized by minor to major changes in species richness and abundance. Planktonic foraminifera are common and diversified below the Selli Level, being the assemblage composed by hedbergellids, few leupoldinids and globigerinelloidids. A similar composition in terms of species richness is recorded within the Selli Level, whereas abundance shows a marked decline. The planktonic foraminiferal assemblage above the Selli is characterised by the occurrence of common hedbergellids, clavate hedbergellids, leupoldinids and both globular and elongate globigerinelloidids. An increase in shell size of the planispiral taxa is also observed. Planktonic foraminifera at Site 463 are generally poorly preserved and rare or absent, especially below and within the Selli Level equivalent. An increase in abundance is observed in the interval above the Selli Level. Comparison with calcareous nannoplankton abundance data highlights significant similarities and differences: 1) ...